From the educational to professional supervision - Berasaluze Correo, Ainhoa; Ariño altuna, Miren (Cuadernos de Trabajo Social, 2014)
This article aims to reflect on the educational and professional supervision as a teaching-learning methodology where education was employed during the formative stage and once this one is completed, the professional supervision is developed with the professional activity. From this point of view, there are two forms of supervision, that sharing much of the constituent elements, they are mainly characterized by the purpose and the specific functions of each of them. In order to contrast this claim, and taking the educational supervision as the axis around which the reflection spins, we will try to identify and incorporate elements that are commonly used in professional supervision, but it certainly can be used in the development of the process of educational supervision. Our purpose, therefore, is to approach the educational supervision during the learning period as a type of initial supervision, principal element of the help professions. After completion of the studies and started working life, continuity is given with the professional supervisión.
Keywords: Social Work; university learning; social intervention; help professions; supervision